Influence of creatine supplementation on indicators of glucose metabolism in skeletal muscle of exercised rats - Araújo, Michel Barbosa de [UNESP]; Vieira Jr., Roberto Carlos; Moura, Leandro Pereira de [UNESP]; Costa Jr., Marcelo [UNESP]; Dalia, Rodrigo Augusto [UNESP]; Sponton, Amanda Christine da Silva [UNESP]; Ribeiro, Carla [UNESP]; Mello, Maria Alice Rostom de [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2013)
The purpose of this study was to evaluate the effect of creatine supplementation in the diet on indicators of glucose metabolism in skeletal muscle of exercised rats. Forty Wistar adult rats were distributed into four groups for eight weeks: 1) Control: sedentary rats that received balanced diet; 2) Creatine control: sedentary rats that received supplementation of 2% creatine in the balanced diet; 3) Trained: rats that ran on a treadmill at the Maximal Lactate Steady State and received balanced diet; and 4) Supplemented-trained: rats that ran on a treadmill at the Maximal Lactate Steady State and received creatine supplementation (2%) in the balanced diet. The hydric intake increased and the body weight gain decreased in the supplemented-trained group. In the soleus muscle, the glucose oxidation increased in both supplemented groups. The production of lactate and glycemia during glucose tolerance test decreased in the supplemented-trained group. Creatine supplementation in conjunction with exercise training improved muscular glycidic metabolism of rats.

O objetivo deste estudo foi avaliar o efeito da suplementação de creatina na dieta sobre indicadores do metabolismo glicídico musculoesquelético de ratos exercitados. Quarenta ratos Wistar adultos foram divididos em quatro grupos por oito semanas: Controle: receberam dieta balanceada, mantidos sedentários; Controle Creatina: receberam suplementação de creatina (2%) na dieta balanceada, mantidos sedentários; Treinado: correram em esteira na intensidade da máxima fase estável de lactato e receberam a dieta balanceada e grupo Treinado Suplementado: correram em esteira na intensidade da máxima fase estável de lactato e receberam suplementação de creatina (2%) na dieta balanceada. A ingestão hídrica aumentou e o ganho de massa corporal reduziu no grupo treinado e suplementado. No músculo sóleo, a oxidação de glicose aumentou em ambos os grupos suplementados. A produção de lactato e a glicemia durante teste de tolerância à glicose diminuíram no grupo treinado e suplementado. A suplementação com creatina em conjunto com treinamento físico melhorou metabolismo de glicídico muscular dos ratos.
Influência da suplementação com creatina em indicadores de metabolismo da glucose no músculo esquelético de ratos exercitados
Influencia de la suplementación con creatina sobre indicadores del metabolismo de la glucosa en el músculo esquelético de ratas ejercitadas
Keywords: Glucose tolerance; Physical activity; Somatic index